Analysis of input pump pulse energy optimization for maximum four-wave mixing conversion efficiency in semiconductor optical amplifier - Hosseini, S.; Razaghi, M.; Das, Narottam (The Society of Photo-Optical Instrumentation Engineers, 2012)
We configure the input pump pulse energy of semiconductor optical amplifiers (SOAs) to maximize the four-wave mixing (FWM) conversion efficiency. We simulate the propagation of optical waves in the SOA using the nonlinear propagation equation, taking into account the gain spectrum dynamics, gain saturation, which depends on carrier depletion, carrier heating, spectral hole-burning, group velocity dispersion, self-phase modulation, and two photon absorption. Our simulation results confirm that corresponding to each input probe pulse, there is an input pump pulse with optimum energy that maximizes the FWM conversion efficiency in the SOA. We introduce a pattern for tuning the input pump pulse energy of SOA, which leads to saving the energy in practical applications. We show that the FWM conversion efficiency will decrease when the input pump pulse energy increases from its optimum point. Moreover, for further input pump pulse energies, the width of the generated FWM pulse increases, and its energy will remain constant.